Analysis of The Marketing Mix “Our” Rice Sales On Purchase Satisfaction at The Makassar Branch Of Bulog - Fatmawati Fatmawati; Muhammad Darwis; Aris Baharuddin (Public Resource Innovation Management and Excellence, 2024)
This study aims to determine how the Marketing Mix Analysis of Rice Sales "KITA" Against Purchase Satisfaction at Bulog Branch Makassar became the object of research. This research uses quantitative research. Data collection techniques used are primary data collection documentation and questionnaires. The sample used is the sample formulated by Slovin as many as 80 respondents. The data obtained from the research results were processed using data analysis and using the SPSS version 25 software program which consisted of validity tests, reliability tests on research instruments as well as descriptive statistical analysis techniques and inferential statistical analysis of the data that had been obtained. This is evidenced by the Correlation Test of 0.700 which means that the relationship between the Marketing Mix and Purchase Satisfaction is strong. The Coefficient of Determination Test was obtained at 0.722, which means that the Marketing Mix Analysis of Rice Sales "KITA" on Purchase Satisfaction obtained a value of 72.2% which was included in the high category interval.